Clinicopathological characteristics of light chain proximal tubulopathy in Korean patients and the diagnostic usefulness of immunohistochemical staining for immunoglobulin light chain - Jung, Minsun (BMC Nephrol, 2020)
BACKGROUND: Light chain proximal tubulopathy (LCPT) is a rare paraproteinemic renal disease that has been mostly reported in Western patients. LCPT is characterized by the accumulation of immunoglobulin (Ig)-light chain (LC) in the proximal tubule. Immunohistochemical staining for Ig-LC has not been investigated in the context of LCPT. We reported the clinicopathological characteristics and Ig-LC immunoexpression of patients with LCPT for the first time in Korea. METHODS: We reviewed the clinicopathological findings of 5 Korean patients diagnosed with LCPT between 2016 and 2018. In addition, immunohistochemical staining for κ-LC and λ-LC was conducted on paraffin-embedded tissues. RESULTS: The median age was 63 years, and the male-to-female ratio was 3:2. The primary renal manifestations were either azotemia or tubular proteinuria. All patients were diagnosed with multiple myeloma with monoclonal κ-LC (#1–2) or λ-LC (#3–5) in the serum and urine. Kidney biopsies revealed diverse and subtle alterations of the proximal tubule, including crystallization, vacuolization, and/or swelling. Electron microscopy revealed crystals in patients #1–2 and non-crystalline particles within numerous/large/dysmorphic lysosomes in patients #3–5. Ig-LC restriction was demonstrated in the proximal tubule as κ-type in patients #1–2 and as λ-type in patients #3–5 by immunohistochemistry and immunofluorescence. Immunohistochemical staining showed diffuse positivity to κ- and λ-LC, although immunofluorescent staining for κ-LC was focal and weak. LCPT has diverse clinicopathological characteristics and subtle morphological alterations, which necessitate ancillary tests for diagnosis. CONCLUSIONS: We introduced immunohistochemical staining for Ig-LC as a useful tool for the diagnosis of LCPT, especially in the case of κ-type crystals.